THE EFFORTS OF THE BINMAS UNIT THROUGH GUIDANCE AND EXPLANATION TO PREVENT DRUGS ABUSE IN THE JURISDICTION OF MAGELANG POLICE - Immanuel Andrew Pratama Malau (Police Studies Review, 2022)
This research was motivated by the increase in drug abuse cases that occurred in Magelang district. The purpose of this study was to determine the implementation of guidance and counseling, the influencing factors and efforts to increase the role of the Binmas unit through guidance and counseling in the jurisdiction of the Magelang Police. The concepts and theories used by the author are the concept of counseling guidance, the concept of narcotics abuse, management theory, and competency theory. This study uses a qualitative approach with descriptive analysis research type that explains systematically supported by the data obtained and data collection techniques by interviewing, observing and reviewing documents. Based on the results of the study, the authors found the fact that there were things that had not been fulfilled in accordance with the regulation of the National Police Chief number 21 of 2007. In the implementation, namely the elements and functions of the stages, the efforts made to increase the role, and the factors that influenced the initial conditions were not maximized. and there are still problems. It can be concluded that the guidance and counseling activities of the Binmas unit are not optimal. Suggestions put forward are to utilize existing technology, increase the ability of personnel from knowledge and expertise and increase cooperation again both from within the police agency and outside the police agency.